Prognostic value of histopathological regression in 850 neoadjuvantly treated oesophagogastric adenocarcinomas - Schmidt, Thomas; Sicic, L.; Blank, Susanne; Becker, K.; Weichert, Wilko; Bruckner, Thomas; Parakonthun, Thammawat; Langer, R.; Büchler, Markus W.; Siewert, J.-R.; Lordick, F.; Ott, Katja (British journal of cancer, 2014)
Recently, histopathological tumour regression, prevalence of signet ring cells, and localisation were reported as prognostic factors in neoadjuvantly treated oesophagogastric (junctional and gastric) cancer. This exploratory retrospective study analyses independent prognostic factors within a large patient cohort after preoperative chemotherapy including clinical and histopathological factors.